Self-perception of dentofacial esthetics in complete unilateral cleft lip and palate - Frota, Carolina Martins (2020)
Objective: The purpose of this study was to evaluate the self-perception of dentofacial esthetics of subjects with complete unilateral cleft lip and palate (UCLP) before and after the orthodontic treatment and analyze the correlation with different variables, such as orthodontic treatment finishing, orthodontic burden of care, socioeconomic status, performed or not orthognathic and rhinoplasty surgeries. Methods: Thirty-nine patients with UCLP (20 females, 19 males; mean age=23.3 years, SD=3.8) analyzed their own facial frontal photographs, both in rest and smiling position, taken before (T1) and after comprehensive orthodontic treatment (T2). A visual analogue scale of facial esthetics satisfaction containing scores divided into 3 groups was used: esthetically unpleasant (1 to 3), esthetically acceptable (4 to 6) and esthetically pleasing (7 to 9). Participants also identified their main complaints. Information regarding socioeconomic status, orthodontic treatment burden of care, need of orthognathic surgery and rhinoplasty were obtained in their medical records. Posttreatment dental models were analyzed using OGS index in order to determine the quality of orthodontic finishing. Interphase changes for self-perception score was analyzed using Wilcoxon tests. Correlation between posttreatment self-perception score and other variables were assessed using Spearman test and differences between sexes were analyzed using Mann-Whitney test (p<0.05). Results: Self-perception improved from esthetically acceptable before treatment to esthetically pleasing after treatment (p<0.001). Males had higher grades than females at T2 (p=0.028). The facial main complaint was nose asymmetry at T1 (87.18%) and T2 (84.61%). No correlation between the analyzed variables and the score for posttreatment facial self-perception was found. Conclusion: The improvement of the dentofacial esthetics self-perception following orthodontic treatment was noticeable. After orthodontic treatment, males presented more satisfaction regarding facial appearance than females. Nose asymmetry was the most frequent complaint before and after treatment